Preparation of a non‐woven poly(ε‐caprolactone) fabric with partially embedded apatite surface for bone tissue engineering applications by partial surface melting of poly(ε‐caprolactone) fibers. Issue 7 (3rd April 2017) - Kim, In Ae; Rhee, Sang‐Hoon
Abstract: This article describes a novel method for the preparation of a biodegradable non‐woven poly(ε‐caprolactone) fabric with a partially embedded apatite surface designed for application as a scaffold material for bone tissue engineering. The non‐woven poly(ε‐caprolactone) fabric was generated by the electro‐spinning technique and then apatite was coated in simulated body fluid after coating the PVA solution containing CaCl2 ·2H2 O. The apatite crystals were partially embedded or fully embedded into the thermoplastic poly(ε‐caprolactone) fibers by controlling the degree of poly(ε‐caprolactone) fiber surface melting in a convection oven. Identical apatite‐coated poly(ε‐caprolactone) fabric that did not undergo heat‐treatment was used as a control. The features of the embedded apatite crystals were evaluated by FE‐SEM, AFM, EDS, and XRD. The adhesion strengths of the coated apatite layers and the tensile strengths of the apatite coated fabrics with and without heat‐treatment were assessed by the tape‐test and a universal testing machine, respectively. The degree of water absorbance was assessed by adding a DMEM droplet onto the fabrics. Moreover, cell penetrability was assessed by seeding preosteoblastic MC3T3‐E1 cells onto the fabrics and observing the degrees of cell penetration after 1 and 4 weeks by staining nuclei with DAPI. The non‐woven poly(ε‐caprolactone) fabric with a partially embedded apatite surface showed good water absorbance, cell penetrability, higher apatite adhesion strength, and higher tensile strength compared with the control fabric. These results show that the non‐woven poly(ε‐caprolactone) fabric with a partially embedded apatite surface is a potential candidate scaffold for bone tissue engineering due to its strong apatite adhesion strength and excellent cell penetrability. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 1973–1983, 2017.